Análises das ocorrências anômalas de fluoreto em águas subterrâneas - Santiago, Mariana Ribeiro (2010)
The present work shows a discussion about the problematic related to the anomalies of fluoride concentrations in groundwaters intended for human provisioning and also about the public health issues and financial waste generated by them. As a contribution, a map was elaborated containing the spacing of the occurrences of anomalous fluoride in the states of Rio Grande do Sul and Santa Catarina. Taking in to account the importance of understanding a little more about the behavior of the waters which suffer this anomaly of fluoride concentration, we have carried out a detailed description of the compositions and of the polytypes of water, verifying what tendencies they present. For that, the area of study has been split in three zones composing the Gurany Aquiferous System: Zones of Blooming, Confinement and Strong Confinement, with a greater emphasis to the Blooming Zone, once that the later presents the greatest amount of wells with excessive fluoride concentrations in the same area, which coincides with the Central Depression of Rio Grande do Sul. After evaluating the typologies of the analyzed waters it was possible to verify the occurrence of a higher tendency in the three zones for the polytype of the sodic Bicarbonate waters. On the basis of the verifications of previous studies attesting the existence of flotations of chemical parameters in underground areas this study has evaluated and identified its percentage of variation in 17 physical-chemical parameters. For that, multivariate data analyses were accomplished for 13 water samples of a deep tubular well (276m), monitored during a six months period, reaching variations of 1,5 200%. The most variable pattern was color. In it was possible to verify that during the pumping period of 15 minutes there has been a coloring variation of water of six different colors attesting how important it is to consider same water taking in order to monitor deep tubular wells because it can receive several water contributions with differentiated characteristics among each other. The pH has shown the smallest percentage of variation, always remaining with the characteristics of neutral pH.